Limiting Rules in the Implementation of Islamic Law: An Analysis of the Principle of Rukhsah and the Hierarchy of Obligations in Contemporary Contexts - Wahid, Khaerunnisa; Fatimah, Nurul; Musyahid, Achmad; Kuba, Imran Anwar (ALSYS, 2025)
This article examines the role of key Islamic jurisprudential principles as constraints in the application of Islamic law, particularly in situations involving emergencies or conflicting obligations. It focuses on two foundational rules: al-rukhaṣ lā tunāṭ bi al-maʿāṣī (legal relief does not apply to immorality) and al-wājib lā yutraq illā li-wājib (an obligation may not be abandoned except for the sake of another obligation). Through a library-based research method, the study analyzes the meanings, sources, and practical relevance of these principles by discussing contemporary scenarios such as invoking rukhṣah during sinful travel, postponing prayer due to urgent medical duties, and balancing academic commitments with the obligation of Friday prayer. The findings highlight the significance of employing the principles of caution (iḥtiyāṭ) and prioritization (tartīb al-awlawiyyāt) in legal istinbāṭ (derivation). These limiting principles serve to protect the integrity of Sharia from the misuse of emergency concessions while promoting justice, public benefit (maṣlaḥah), and alignment between scriptural texts and real-life contexts. The integration of these rules is essential for formulating contextual Islamic legal responses that remain faithful to ethical and evidentiary foundations of Sharia.